2019
DOI: 10.1111/ddi.12969
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dispersal is a critical element of concordance between biophysical dispersal models and spatial genetic structure in Great Barrier Reef corals

Abstract: Aim: Widespread coral bleaching, crown-of-thorns seastar outbreaks, and tropical storms all threaten foundational coral species of the Great Barrier Reef, with impacts differing over time and space. Yet, dispersal via larval propagules could aid reef recovery by supplying new settlers and enabling the spread of adaptive variation among regions. Documenting and predicting spatial connections arising from planktonic larval dispersal in marine species, however, remains a formidable challenge. Location:The Great B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 77 publications
4
26
0
Order By: Relevance
“…Across all of these models migration coefficients were larger for the southward direction. Although this is against the predominant direction of inshore current flow 48 and predicted movement from biophysical models 49 it is in accordance with studies that have shown southward migration to be the predominant direction of gene flow for A. tenuis and A. millepora on the GBR 9,49 including for inshore populations. This disconnect between biophysical modelling (which reflects northward inshore currents) and southward gene flow could reflect differences in effective population size.…”
Section: Demographic Historysupporting
confidence: 89%
“…Across all of these models migration coefficients were larger for the southward direction. Although this is against the predominant direction of inshore current flow 48 and predicted movement from biophysical models 49 it is in accordance with studies that have shown southward migration to be the predominant direction of gene flow for A. tenuis and A. millepora on the GBR 9,49 including for inshore populations. This disconnect between biophysical modelling (which reflects northward inshore currents) and southward gene flow could reflect differences in effective population size.…”
Section: Demographic Historysupporting
confidence: 89%
“…Across all of these models, migration coefficients were larger for the southward direction. Although this is against the predominant direction of inshore current flow (35) and predictions based on biophysical modeling (36), it is consistent with studies that have shown southward migration to be the predominant direction of gene flow for A. tenuis and A. millepora on the GBR (6,36) including for inshore populations. This disconnect between biophysical modeling (which reflects prevailing, but variable, northward inshore currents) and apparent gene flow could reflect differences in effective population size.…”
Section: And Table S2supporting
confidence: 89%
“…Over the last four decades, we have assembled extensive knowledge on the genetic characterization of marine organisms, mainly concerning the spatial distribution and structuring of populations (e.g., Knutsen et al, 2007;Plank et al, 2010;Robalo et al, 2013;Riginos et al, 2019;Verry et al, 2020). With this information, it is now possible and relevant to understand how these patterns behave through time.…”
Section: Introductionmentioning
confidence: 99%